Supramolecular soft matter : applications in materials and organic electronics - Nakanishi, Takashi (Hoboken, N.J. : John Wiley & Sons, 2011)
'This book covers molecular design and synthesis, as well as the development of smart molecular assemblies, for organic electronic systems. It identifies concepts that hold promise for successful development of organic/polymeric electronics with real-world applications. Unlike other books, this is not simply a compilation of current trends in supramolecular soft matter. The chapters, written by leading researchers, help readers understand and manipulate the electronic properties of supramolecular soft materials for use in organic electronic devices, such as photovoltaics and field effect transistors, some of the most desired materials for energy conservation'--
'This book covers molecular design and synthesis, as well as the development of smart molecular assemblies, for organic electronic systems'--
Keywords: Supramolecular electrochemistry; Molecular structure; Molecular biology